Family Support With The Level of Preschool Children Anxiety in the Intravenous Installation - Pardede, Jek Amidos; Simangunsong, Madya Mangun (Jurnal Keperawatan Jiwa, 2020)
Children who are hospitalized will experience anxiety because of facing invasive actions such as intravenous installation in the hospital. Anxiety makes children feel weak so that they make children cry, scream, and fight. Overcoming this level of anxiety requires family support to relieve the pressure felt by the child. This study aims to identify the relationship of family support with the level of anxiety of children at the time of intravenous installation. The design of this study used descriptive corrosion with a monthly population of 44 people and the sampling technique was done by accidental sampling technique, as many as 40 respondents of preschool children aged 3-6 years. The data collection tool uses a questionnaire. The results showed that the support given by the family to children was a good majority of 27 people (67.5%) and there was a moderate majority anxiety level of 26 people (65%) with a p-value = 0,000 <0.05 and there is a significant relationship between family support and the anxiety level of preschool children at the time of intravenous installation in the emergency room at Sari Mutiara Hospital in Medan.